Manajemen Pembelajaran Tematik Terpadu di SDN 1 Karangasem Wirosari Grobogan - Utami, Retno Tyas; , Prof. Dr. Abdul Ngalim, M.M, M.Hum; , Dr. Sumardi, M.Si (2016)
The purpose of this study to describe (1) Planning of integrated thematic learning at SDN 1 Karangasem Wirosari Grobogan. (2) The implementation of integrated thematic learning at SDN 1 Karangasem Wirosari Grobogan. (3) Evaluation of integrated thematic learning at SDN 1 Karangasem Wirosari Grobogan. This research was qualitative. Held at SDN 1 Karangasem Wirosari Grobogan. Data collection methods used are observation, interviews, and documentation. Test the validity of the data in this study, using triangulation techniques. The results of the study are (1) Planning begins with the preparation of lesson plans, teacher planning materials, teaching methods, instructional media, learning resources and assessment techniques used. Equipped learning activity that contains the introduction, core activities, and cover with the time allocation in accordance with the competencies, learning objectives and allocation of available time. (2) Implementation of learning is good , covering planning capabilities open lessons , presenting the material , using methods / media , using props , using communicative language , motivate students , organizing activities , interact with students in a communicative , concluded learning , providing feedback , providing an assessment , and the use of time. (3) The evaluation was appropriate learning lesson preparation ( syllabus , RPP ) with steps evaluation of learning that evaluation planning , evaluation , evaluation data processing , and reporting the results of the evaluation.